UNA MICROFLORA DEL TRIASICO SUPERIOR DE LA CUENCA DE MALARGUE, LOCALIDAD LLANTENES, PROVINCIA DE MENDOZA, ARGENTINA (Ameghiniana, 2013)
AN UPPER TRIASSIC MICROFLORA FROM THE MALARGUE BASIN, LLANTENES LOCALITY, MENDOZA PROVINCE, ARGENTINA. In the lower part of the continental Chihuido Formation, Malargüe Basin, Llantenes locality, a microflora was found with prevailing non-striate bisaccate pollen grains (Alisporites, Podocarpidite, Falcisporites) and fresh water microplankton. Taxa characteristic for the Triassic, like Guthoerlisporites cancellosus, striate bisaccate pollen and Polypodiisporites ipsviciensis are associated with the first representatives of the genus Classopollis, a genus which in Argentina becomes frequent in the Early Jurassic. Other characteristic genera of the Llantenes microflora are Leptolepidites, Gemmatriletes, Deltoidospora, Auritulinasporites, Dictyophyllidites, Biretisporites, Neoraistrickia, Baculatisporites, Verrucosisporites, Equisetosporites and Cycadopites. The presence of the genus Classopollis, together with exclusively Triassic taxa suggests that this microflora is, among all the Triassic microfloras known from Argentinian sedimentary basins (Cuyo Basin, Ischigualasto- Villa Union-Basin) the youngest one. The Llantenes microflora is associated with plant megafossils (including large trunks). From both the Chihuido Formation and the Tronquimalal Formation, which covers conformably the former, a Triassic Dicroidium flora is known.